Gastrografin may reduce time to oral diet in prolonged post‐operative ileus: a pooled analysis of two randomized trials. Issue 7 (6th March 2018) - Milne, Tony G. E.; Vather, Ryash; O'Grady, Gregory; Miquel, Jordi; Biondo, Sebastiano; Bissett, Ian
Abstract : Background: Gastrografin has been suggested as a rescue therapy for prolonged post‐operative ileus (PPOI) but trial data has been inconclusive. This study aimed to determine the benefit of gastrografin use in patients with PPOI by pooling the results of two recent randomized controlled trials assessing the efficacy of gastrografin compared to placebo given at time of PPOI diagnosis. Methods: Anonymized, individual patient data from patients undergoing elective bowel resection for any indication were included, stoma closure was excluded. The primary outcome was duration of PPOI. Secondary outcomes were time to tolerate oral diet, passage of flatus/stool, requirement and duration of nasogastric tube, length of post‐operative stay and rate of post‐operative complications. Results: Individual patient data were pooled for analysis (53 gastrografin, 55 placebo). Gastrografin trended towards a reduction in PPOI duration compared to placebo, respectively, median 96 h (interquartile range, IQR, 78 h) versus median 120 h (IQR, 84 h), however, this result was non‐significant ( P = 0.11). In addition, no significant difference was detected between the two groups for time to passage of flatus/stool ( P = 0.36) and overall length of stay ( P = 0.35). Gastrografin conferred a significantly faster time to tolerate an oral diet compared to placebo (median 84 h versus median 107 h, P = 0.04). There was no difference in post‐operative complications between the two interventions ( P > 0.05). Conclusion: Gastrografin did not significantly reduce PPOI duration or length of stay after abdominal surgery, but did reduce time to tolerate a solid diet. Further studies are required to clarify the role of gastrografin in PPOI.